18th edition IET wiring regulations. Design and verification of electrical installations - Scaddan, Brian (Abingdon, Oxon : Routledge/Taylor & Francis Group, 2019)
"This popular guide provides an understanding of basic design criteria and calculations, along with current inspection and testing requirements and explains how to meet the requirements of the IEE IET Wiring Regulations. The book explains in clear language those parts of the regulations that most need simplifying. There are common misconceptions regarding bonding, voltages, disconnection times and sizes of earthing conductors. This book clarifies the requirements and outlines the correct procedures to follow. This title provides an affordable reference for all electrical contractors, technicians and other workers involved in designing and testing electrical installations. The content covers the requirements for both City & Guilds and EAL courses, and contains sample exam questions and answers. It also makes an ideal revision guide"--
"First edition published 1995 by Newnes, an imprint of Elsevier."
Includes bibliographical references and index.
Keywords: Electric wiring, Interior -- Handbooks, manuals, etc; Electric wiring -- Insurance requirements -- Handbooks, manuals, etc; Electric apparatus and appliances -- Installation -- Handbooks, manuals, etc; Electric wiring -- Insurance requirements -- Great Britain -- Handbooks, manuals, etc